On the Investigation of the Droplet–Droplet Interactions of Sodium 1, 4‐Bis(2‐ethylhexyl) Sulfosuccinate Reverse Micelles upon Changing the External Solvent Composition and Their Impact on Gold Nanoparticle Synthesis (Eur. J. Inorg. Chem. 27/2014). Issue 27 (September 2014) - Gutierrez, Jorge A.; Falcone, R. Dario; Lopez‐Quintela, M. Arturo; Buceta, David; Silber, Juana J.; Correa, N. Mariano
Abstract : The inside cover picture shows the high versatility of reverse micelles as nanoreactors. The composition of the nonpolar organic medium has a huge effect on properties such as the interfacial micropolarity, the hydrogen‐bonding ability, and the sequestrated water structure of sodium 1, 4‐bis(2‐ethylhexyl)sulfosuccinate (AOT) reverse micelles (RMs). Therefore, not only gold nanoparticles (in n ‐heptane) but also evidence of subnanometer clusters (in benzene) was obtained by using RMs as nanoreactors. The results are very promising for many applications. Details are discussed in the article by N. M. Correa et al. onp. 2095 ff .